The aircraft designers a Grumman historical perspective - Ciminera, Michael V. (Library of flight, 2013)
Tells the behind-the-scenes story of the designers and engineers who conceived and built Grumman aircraft from the founding of the company in 1929 until its 1994 acquisition by Northrop. This book also identifies key team members who contributed to the creation and development of each new design.